2019
DOI: 10.1530/erc-19-0129
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotoxicosis with concomitant thyroid cancer

Abstract: Thyrotoxicosis with concomitant thyroid cancer is rare and poorly recognized, which may result in delayed diagnosis, inappropriate treatment and even poor prognosis. To provide a comprehensive guidance for clinicians, the etiology, pathogenesis, diagnosis and treatment of this challenging setting were systematically reviewed. According to literatures available, the etiologies of thyrotoxicosis with concomitant thyroid cancer were categorized into Graves’ disease with concurrent differentiated thyroid cancer (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 136 publications
(206 reference statements)
0
14
0
1
Order By: Relevance
“…The mechanism here is thought to be related to increased type 1 and type 2 iodothyronine deiodinase activity in tumour tissue. (8,10) In this patient, we propose that both the extensive bulky metastatic disease and subsequent deiodination from T4 to T3 as reasons for hyperthyroidism.…”
Section: Discussionmentioning
confidence: 87%
“…The mechanism here is thought to be related to increased type 1 and type 2 iodothyronine deiodinase activity in tumour tissue. (8,10) In this patient, we propose that both the extensive bulky metastatic disease and subsequent deiodination from T4 to T3 as reasons for hyperthyroidism.…”
Section: Discussionmentioning
confidence: 87%
“…26 With regards our case, it is important to highlight the atypical presentation of this rare carcinoma, that is, the incidence of hyperthyroidism, which is not considered to be one of the primary symptoms of thyroid cancer. 27 The association between thyrotoxicosis and thyroid cancer is rare and little-recognized, which can lead to a delay in the diagnosis of this tumor and, consequently, to a worse prognosis. Even so, an increasing number of studies have been carried out which demonstrate that this association is possible and that a careful assessment of the thyroid gland is essential whenever any thyroid dysfunction is detected.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, an increasing number of studies have been carried out which demonstrate that this association is possible and that a careful assessment of the thyroid gland is essential whenever any thyroid dysfunction is detected. 27 The most commonly reported presentation of MMFTC is a slowly increasing swelling of the neck. [28][29][30] In most cases, lymph node metastases were reported at diagnosis, as a single tumor cell population, or, alternatively, as a mixture of both components within the same lymph node.…”
Section: Discussionmentioning
confidence: 99%
“…There are reported cases of thyrotoxicosis associated with ATC, which show that the etiologies are nonspecific, such as ATC associated with Graves’ disease, autonomous thyroid nodules, and silent thyroiditis ( 19 ). Due to the clinical and radiological characteristics of our case report, we postulate that the rapid invasion and destruction of normal thyroid follicle cells by malignant tumor cells, resulting in the leakage of preformed hormones into the circulation, was the main etiology of thyrotoxicosis, a finding that has been previously reported in patients with rapidly growing ATC ( 4 , 19 , 20 , 21 ), cases in which TPO antibody results have been negative. However, Heyman et al reported a 74-year-old man who was presented with left-sided neck pain and a rapidly enlarging neck mass.…”
Section: Discussionmentioning
confidence: 99%